Quality of Life and the Degree of Disease Acceptance In Patients with Spinocerebellar Ataxia - Magdalena Kazimierska-Zając; Robert Dymarek; Joanna Rosińczuk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Spinocerebellar ataxias (SCA) belong to a group of rare genetic diseases. They are characterized by the multiplicity of symptoms, of which the most characteristic is limb ataxia and dysarthria. The disease progresses over time, leading to severe disability. So far an effective method of treating SCA has not been invented. Aim. The main purpose was to analyze the quality of life and the level of disease acceptance in patients with SCA. Material and Methods. The study included 70 patients with the average duration of SCA of approximately 13 years. The age of patients ranged from 26 to 81 years (mean 50±10 years). All participants were examined using the Acceptance Illness Scale (AIS) and the Health Survey (SF-36). Statistically significant differences in the degree of disease acceptance were observed in patients who differed in terms of education level and gender. Results. In the physical sphere, women assessed their life quality more favorably than men (p=0.040), however, men declared better scores in bodily pain (p=0.017). It was observed that, in the sphere of mental health, men were more peaceful, and women were believed in deterioration of their health condition (p=0.039). Patients with SCA exhibit a very low level of both, disease acceptance and the quality of life. Women worse than men accept the disease, and they feel useless more often. The higher level of disease acceptance is shown by patients with higher education than those with vocational education. An interpersonal relationships get worse, especially among men, however, women often feel useless. Patients with SCA rate their life quality very low. Conclusions. It is necessary to educate patients, their caregivers, medical staff in order to develop desirable health behaviors. Understanding this rare disease will help improve the quality of life and therefore will improve the level of disease acceptance. (JNNN 2018;7(1):12–21)